A novel study on seismic response of base-isolated wind turbine taking the soil-structure interaction impact - Mellas, Nesrine; Mellas, Mekki; Mabrouki, Abdelhak; Hebbache, Kamel; Alemdar, Zeynep Firat (TAYLOR & FRANCIS INC, 2026)
This study introduces an innovative approach by applying seismic isolation to the base of wind turbines, a strategy that has received limited attention in the field. The primary objective of this study is to evaluate the effectiveness of leaded Rubber Bearing Isolator (LRB) in reducing vibrations and redistributing dynamic forces under seismic loads. This evaluation will be achieved by integrating the effect of soil-structure interaction (SSI). A model of an 8 MW wind turbine in homogeneous stiff clay soil is developed using SAP2000 software, with SSI evaluated through the implementation of Winkler's model. The findings demonstrate that LRB isolators enhance seismic performance and mitigate fatigue damage, extending the operational lifespan of wind turbines. The seismic analysis demonstrates the efficacy of LRB isolators in substantially mitigating acceleration and base forces. Furthermore, the study underscores the significance of optimizing damping ratios to ensure optimal isolation performance under variable seismic conditions. The ensuing results are presented and compared for various scenarios, including configurations with and without isolators, as well as variations in damping ratio. This research offers novel insights into the utilization of seismic base isolators for wind turbines, thereby enhancing their resilience to earthquakes, particularly in regions with elevated seismic risk.
Keywords: Wind turbine; LRB isolator; damping ratio; SSI; beam on Winkler foundation; SAP2000; dynamic loading; TUNED MASS DAMPERS; VIBRATIONS; Engineering; Oceanography; Mining & Mineral Processing